Platelet-Rich Plasma Combined With Autologous Grafting in the Treatment of Long Bone Delayed Union or Non-union: A Meta-Analysis - An, Weijun; Ye, Peng; Zhu, Tao; Li, Zhizhong; Sun, Jianbin (Frontiers in Surgery, 2021)
Background: Platelet-rich plasma (PRP) has been suggested as an emerging treatment for bone defects. However, whether PRP could enhance the therapeutic efficacy of autologous bone grafting for long bone delayed union or nonunion remains unknown. A meta-analysis of randomized and non-randomized controlled trials (RCT and NRCT) was performed to summarize current evidence. Methods: Relevant RCTs and NRCTs comparing the influences of autologous bone grafting on healing of long bone delayed union or nonunion with and without PRP were obtained by search of PubMed, Embase, Cochrane’s Library, China National Knowledge Infrastructure, and WanFang databases from inception to September 10, 2020. A random-effect model was applied to pool the results with the incorporation of the potential heterogeneity. Subgroup analysis according to study design was also performed. Results: Six RCTs and two NRCTs with 420 patients were included. Compared to patients allocated to autologous bone grafting alone, those allocated to a combined treatment with PRP and autologous bone grafting was not associated higher rates of radiographic bone healing (risk ratio [RR]: 1.06, 95% confidence interval [CI]: 0.99 to 1.13, P=0.09; I2=24%) or excellent/good post-treatment limb function (RR: 1.14, 95% CI: 0.95 to 1.37, P=0.37; I2=0%), but was associated with a shorter healing time (mean difference: -1.35 months, 95% CI: -1.86 to -0.84, P<0.001; I2=58%). Subgroup analysis according to study design showed similar results for the above outcomes (P values for subgroup difference all >0.10). Conclusions: Combined treatment with PRP and autologous bone grafting may be effective to accelerate the healing of long-bone delayed union or nonunion compared to autologous bone grafting alone.